Conservation of Tiger Nut Tubers with Natural Biofilm Formulated with Thymus zygis Essential Oil - Santamarina, M. Pilar (2025)
Cyperus esculentus L. var sativus is cultivated in Spain, only in the L’Horta Nord in the Valencia region. In this country, tubers are consumed fresh to make a popular beverage in the Valencia region called “horchata de chufa” (chufa milk). This drink is considered beneficial for human health thanks to its high nutritional value and medicinal importance in several treatments. This work evaluates the antifungal potential of the Thymus zygis essential oil against fungi found in tiger nut warehouses to preserve tubers under the best conditions. The analyzed commercial thyme essential oil belongs to the thymol/pcymene/ γ-terpinene chemotype. Thymol was found in larger quantities (51.34%), followed by the identified biogenetic precursors p-cymene (35.16%) and γ-terpinene (3.53%). Carvacrol also appeared, but in small quantities (3.53%). During in vitro tests, the T. zygis EO showed strong inhibition (98.85% to 91.81% MGI) against fungi Alternaria alternata, Fusarium andiyazi, Fusarium incarnatum, and Fusarium oxysporum at 300 μg/mL. It totally inhibited their growth (100% MGI) at 400 μg/mL, and did so strongly (75.94%, 72.02%, and 70.78%) with fungi Podospora australis, Penicillium commune, and Cladosporium subuliforme, respectively. Under in vivo conditions, formulated as a protective biofilm, and by forcing the environmental conditions of temperature and humidity to the maximum for fungus F. andiyazi growth on tiger nut tubers, the created film acted as a strong protector against fungal attacks.